Ðž Ð²Ñ‹ÑÐ¾ÐºÐ¸Ñ… ÑÐºÐ¾Ñ€Ð¾ÑÑ‚ÑÑ… Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸Ñ Ð¸ Ð¾Ñ…Ð»Ð°Ð¶Ð´ÐµÐ½Ð¸Ñ Ð±Ð¸Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ð¾Ð±ÑŠÐµÐºÑ‚Ð¾Ð² Ð² Ñ†Ð¸Ð»Ð¸Ð½Ð´Ñ€Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… ÐºÐ¾Ð½Ñ‚ÐµÐ¹Ð½ÐµÑ€Ð°Ñ… Ð¿Ñ€Ð¸ Ð¸Ñ… Ð¿Ð¾Ð³Ñ€ÑƒÐ¶ÐµÐ½Ð¸Ð¸ Ð² Ð¶Ð¸Ð´ÐºÐ¸Ð¹ Ð°Ð·Ð¾Ñ‚ - Babenko, V. I.; Grischenko, V. I.; Dunayevskaya, A. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
The heat transfer in multicomponent cryoprotective media under high cooling rates in cylindrical containers was experimentally and theoretically studied. As the medium model 1M phosphate buffer glycerol solution was used.